2008
DOI: 10.2109/jcersj2.116.1319
|View full text |Cite
|
Sign up to set email alerts
|

Pressureless sintering of boron carbide ceramics

Abstract: Densification of boron carbide (B4C) was studied by pressureless sintering at temperatures ranging from 2108° to 2226°C with Al gas and Si compound gas derived from SiC. High purity boron carbide compacts attained a bulk density of a nearly full density (2.455 g/cm 3 ) after being sintered at 2226°C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 12 publications
1
20
0
Order By: Relevance
“…In this study, B 4 C ceramics for use in high-temperature applications were joined using foils of refractory metals such as Ti and Mo. He investigated the joining of B 4 C ceramics at 1500°C over a period of 10 h under a pressure of 18.6 MPa using various foils.…”
Section: Cockerammentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, B 4 C ceramics for use in high-temperature applications were joined using foils of refractory metals such as Ti and Mo. He investigated the joining of B 4 C ceramics at 1500°C over a period of 10 h under a pressure of 18.6 MPa using various foils.…”
Section: Cockerammentioning
confidence: 99%
“…It is well known that Al has a low melting point, which is 660°C, and that it is an effective sintering additive for the preparation of B 4 C ceramics. 4)6) Kumazawa et al 4) reported that B 4 C compacts were pressurelessly sintered using Al gas and a Si compound gas derived from SiC. Miyazaki et al 5) studied the microstructure of B 4 C ceramics pressurelessly sintered in an Ar atmosphere containing Al gas and a Si-compound gas.…”
Section: Cockerammentioning
confidence: 99%
See 1 more Smart Citation
“…2) Nowadays, large-sized B 4 C ceramics are required for stages and table of steppers, which are one of the semiconductor manufacturing equipments. Steppers are an essential part of the semiconductor manufacturing process, called photolithography, which creates millions of microscopic circuit elements on the surface of tiny chips of Si.…”
Section: Introductionmentioning
confidence: 99%
“…However, this method is not suitable for manufacturing large-sized and complicated components from the viewpoint of energy saving and production efficiency. Joining of B 4 C ceramics is considered as one of the promising and effective approaches for producing B 4 C components for such applications.…”
Section: Introductionmentioning
confidence: 99%